Optical Coherence Tomography: An Eye Into the Coronary Artery - Gupta, Ankush; Shrivastava, Abhinav; Vijayvergiya, Rajesh; Chhikara, Sanya; Datta, Rajat; Aziz, Atiya; Singh Meena, Daulat; Nath, Ranjit Kumar; Kumar, J. Ratheesh (Frontiers in Cardiovascular Medicine, 2022)
Optical coherence tomography (OCT) has been slowly but surely gaining a foothold into the hands of the interventional cardiologist. Intra-luminal and trans-mural contents of the coronaries remain no longer elusive to the probing eye of the cardiologist. Although the graduation of an interventionalist in imaging techniques right from the naked eye angiographies to the ultrasound based coronary sonographies to the modern light-based OCT has been slow, but with the increasing regularity of complex coronary cases in practice, such a transition is inevitable. Although Intravascular ultrasound (IVUS) due to its robust clinical data has been the preferred imaging modality in recent years, OCT provides a distinct upgrade over it in many imaging and procedural aspects. Better image resolution, accurate estimation of calcified lesion, better acute and chronic stent failure evaluation are the distinct advantages of OCT over IVUS. Despite the obvious imaging advantages an OCT provides, clinical impact of OCT remains subdued. However upcoming newer trials and data have been encouraging for expanding the use of OCT to wider indications in clinical utility. During PCI, OCT provides detailed information (dissection, tissue prolapse, thrombi, and incomplete stent apposition) required for optimal stent deployment which holds the key to successfully reducing the MACE and stent related morbidities. OCT is being studied in its increasing utilization in complex bifurcation stenting involving the left main. Also, the traditional pitfalls of an OCT like extra contrast load for image acquisition, stenting involving the ostial and proximal left main have also been overcome recently and is discussed. In this review we discuss the OCT image interpretation and its clinical impact on the outcome of procedures along with the current barriers to its use and the newer paradigms where the OCT is starting to become a promising tool for the interventionalist and what to expect for the immediate future in the world of imaging.